PENGARUH PENDAPATAN USAHA, BIAYA OPERASIONAL DAN PERPUTARAN TOTAL AKTIVA TERHADAP LABA BERSIH PADA PT MEGA CENTRAL AUTONIAGA MEDAN PERIODE 2013-2017 - ENDANG KURNIATI (JURNAL ILMIAH KOHESI, 2019)
Every company basically has a variety of different objectives. The goal is to increase profits, increase employee productivity, improve employee satisfaction and coaching, and the most important is how the company generates profits as large as. Financial performance assessment can be used to find out how much the company profits by comparing. The purpose of this study is to find out and analyze the "Effect of Business Income, Operational Costs and Total Asset Turnover on Net Profit at PT Mega Central Autoniaga Medan for the 2013-2017 Period. The method used in this study is descriptive analysis method by describing or describing the data that has been collected as it is without the intention to make conclusions that apply to the general or generalization. The data analysis method used is Multiple Linear Regression using SPSS software. The results of the study show that business income, operational costs and total assets turnover simultaneously have a positive and significant effect on net income at PT Mega Central Autoniaga Medan for the 2013-2017 period. In the coefficient of determination Adjusted R2 value obtained at 30.4% means variable variations in business income, operational costs and total assets turnover can explain the effect on net profit while the remaining 69.6% is a variation of other variables not explained in this study for example capital etc. Business income partially has a positive and significant effect on net income at PT Mega Central Autoniaga Medan for the 2013-2017 period